A pedagogia cultural do Carimbloco do Pacoval: cultura local, memória e identidade - MALATO, Karla Roberta de Souza (2024)
This text presents the cultural pedagogy of the pacoval carimbloco: local culture, memory and identity, supported by bibliographical research and fieldwork, using the qualitative approach and some theoretical contributions such as Godoy (1995), Klein and Domenico (2012), Lakatos and Marconi (1992), among others who contributed to the development of the article, thus seeking the relationships established between the concepts of education and their significance in the context carnivalesque, aiming to describe through research the socio-historical context of the carimbloco and its possible relationship with educational, social and cultural, in a carimbloco pedagogy where teaching and learning become fundamental in a non-school environment. Reaching out through workshops people who know and don't know about the local carimbó culture, causing a learning of meanings in which everyone gets involved, participating in every moment provided by the workshops, developing a bond that goes eyond race, gender, religion, ethnicity, etc